Um estudo comparativo entre as políticas de assistência estudantil da UFT e IFTO: - Souza, Juliana Abrunhosa Resende (Universidade Federal do Tocantins, 2022)
The university in Brazil has its origin linked to the elitist interests, where the first higher courses were directed only to the dominant class of the country, but most of these students were to carry out their formation in the great European universities, in front of this, only in Century XX, that the first university is established on national soil, and under the circumstances of the need to grant the title of doctor honoris causa to the King of Belgium. The expansion interests of higher education have been in the background for almost the entire history of Brazil, and with high selectivity, access was restricted to a few, and in this context, the Student Assistance policy did not have a specific plan of action, but with the expansion of Higher Education from the first years of the twenty-first century, became fundamental for the permanence of the new public that began to attend university. This point, what we propose to analyze in the present work the Student Assistance Programs of the Federal Institutions of Higher Education of Palmas, UFT and IFTO, with the purpose of verifying the differences and levels of effectiveness of the policy against the reality of the undergraduate students of the two institutions. For this purpose, this research was based on bibliographic, documentary and field research methodology, in which the questionnaire was applied to the beneficiaries of the programs that form the said policy of each institution.